\left\{ \begin{array} { l } { 2 x + y + 2 z = 3 } \\ { x - 3 y - 2 z = 2 } \\ { 4 x + y + 3 z = 1 } \end{array} \right.
Solve for x, y, z
x=-19
y=-31
z=36
Share
Copied to clipboard
y=-2x-2z+3
Solve 2x+y+2z=3 for y.
x-3\left(-2x-2z+3\right)-2z=2 4x-2x-2z+3+3z=1
Substitute -2x-2z+3 for y in the second and third equation.
x=-\frac{4}{7}z+\frac{11}{7} z=-2-2x
Solve these equations for x and z respectively.
z=-2-2\left(-\frac{4}{7}z+\frac{11}{7}\right)
Substitute -\frac{4}{7}z+\frac{11}{7} for x in the equation z=-2-2x.
z=36
Solve z=-2-2\left(-\frac{4}{7}z+\frac{11}{7}\right) for z.
x=-\frac{4}{7}\times 36+\frac{11}{7}
Substitute 36 for z in the equation x=-\frac{4}{7}z+\frac{11}{7}.
x=-19
Calculate x from x=-\frac{4}{7}\times 36+\frac{11}{7}.
y=-2\left(-19\right)-2\times 36+3
Substitute -19 for x and 36 for z in the equation y=-2x-2z+3.
y=-31
Calculate y from y=-2\left(-19\right)-2\times 36+3.
x=-19 y=-31 z=36
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}